P1824 Feature tracking strain values of noncompaction cardiomyopathy patients: differences in the light of ejection fraction. (17th January 2020) - Kiss, A; Szucs, A; Gregor, Z S; Toth, A; Furak, A; Horvath, M; Czimbalmos, C S; Dohy, Z S; Szabo, L; Suhai, F I; Merkely, B; Vago, H
Abstract: Feature tracking (FT) is a new cardiac magnetic resonance (CMR) technique for strain measurement which may give additional information about the progression of noncompaction cardiomyopathy (NCMP). First in the literature, we compared the strain and functional parameters of NCMP patients with reduced (R) and good (G) ejection fraction (EF) using CMR-FT. From the total of 164 CMR proven R NCMP patients, who were examined between 2009 and 2018 at the Heart and Vascular Center of Semmelweis University, we selected 26 non-ischaemic, contrast agent-free examinations (age: 56 ± 10.6 years; EF: 32.7 ± 10.0%; male = 19). According to their EF they were divided into medium (M; EF: 35-50%; n = 10) and significantly reduced EF (SR; EF <35%; n = 16) subgroups. We searched 25 NCMP patients with good EF (age: 37 ± 14.4 years; EF: 65.9 ± 5.3%; male = 16) and 26 control persons (age: 52 ± 10.7 years; EF: 70.8 ± 5.1%; male = 16) to the above mentioned groups. The Medis Suite program was used for analysis and the MedCalc software for statistics, (p < 0.05). Significant differences were found between the functional parameters of R and G patients. The global longitudinal strain (GLS) and global circumferential strain (GCS) values of the R group were decreased significantly compared to G and C groups. (R vs G; GLS: -9.5 ± 4.3 vs -20.9 + 3.2%; GCS: -12.5 ± 6.1 vs -30.5 ± 5.0%, p < 0.0001; R vs C; GLS: -9.5 ± 4.3 vs -23.3 ± 4.4%; GCS: -12.5 ± 6.1 vs -35.6 ± 5.1%, p < 0.0001). All the segmental strain values of R group were decreased compared to G and C groups, moreover this significancy was observed between the M and SR subgroups as well. The strain values of the R group in all the basal, mid and apical part of the left ventricle (LV) were reduced equally. The average longitudinal strain values of the apical part of the LV in the SR subgroup were significantly reduced compared to the average strains of the basal part (apical vs basal: -8.9 ± 3.0 vs -11.9 ± 4.4 %, p < 0.05). In addition, we found positive correlation in the R subgroup between the GCS and the mass of trabeculated muscle (r = 0.58, p = 0.002) . Our study shows that the global and segmental strain values decreased significantly in proportion to the reduction of the EF which describes well the progression of heart failure in NCMP. However, the decreased strain values of the hypertrabeculated apical part might be specific to NCMP.